12.HISTOPATHOLOGICAL CHARACTERISTICS OF PLEOMORPHIC ADENOMA; A RETROSPECTIVE ANALYSIS OF 120 CASES (Iraqi Journal of Medical Sciences, 2018)
Background: The salivary gland pleomorphic adenoma (PA) is a benign epithelial neoplasm, histologically characterized by a great diversity of morphological aspects. It is the most common neoplasm of salivary gland origin.Objective: Studying the histopathological characteristics of PA with special attention to the various morphological features of the epithelial cells and stromal components of this neoplasm.Methods: Hematoxylin and Eosin (H&E) stained tissue sections of 120 cases of PA were reviewed. The tumors were classified according to their histological subtypes as described by Seifert et al. The epithelial components were analyzed considering the type of cells and the morphological pattern. The stromal components were analyzed according to the presence of myxoid, hyaline, chondroid or calcified tissue.Results: This study revealed that most of the tumors were located in the parotid gland (44%). Myxoid or stroma-rich was the most frequent histological subtype (43%). Plasmacytoid cells were the most commonly seen epithelial component (100%), followed by cuboidal cells in (80%) of the cases. Trabecular pattern was the predominant epithelial morphological pattern (90 %), and the myxoid component was the most frequent stromal component (80%).Conclusion: PA of the salivary glands demonstrates a wide variety of cells, stromal components, and morphological characteristics. Since it is the most frequent salivary gland neoplasm that can resemble other salivary gland tumors, the knowledge about these variations is essential for a correct diagnosis.Keywords: Histopathology, pleomorphic adenoma, salivary gland neoplasmsCitation: Sarkis SA, Al-Drobie BF, MajeedGH, Al-Marzooq TJM.Histopathological characteristics of pleomorphic adenoma; a retrospective analysis of 120 cases. Iraqi JMS. 2018; Vol. 16(1): 84-91. doi: 10.22578/IJMS.16.1.12
Keywords: Histopathology; pleomorphic adenoma; salivary gland neoplasms